Analisis Normatif-Yuridis Tentang Penggantian Nadzir Tidak Cakap Dalam Pengelolaan Wakaf (Studi Putusan Nomor 460 K/AG/2019) - Fatma, Umi (Program Studi Hukum Ekonomi Syariah, 2022)
One of the problems is in the Supreme Court Decision Number 460K/AG/2019 regarding the replacement of Nadzir who is incompetent in waqf management. This study aims to find out how the legal considerations that the judge decided in the case of Decision Number 460 K/AG/2019 regarding the Replacement of Nadzir and to find out how the normative-juridical analysis of the legal considerations of the decision of the Majlis Judges at the cassation level Number 460K/AG/2019 regarding the replacement of Nadzir was made. cancel the decision of the Samarinda Religious High Court Number 36/Pdt.G/2018/PTA.Smd. Methods This research uses the type of library research (library research). Data collection is more emphasized on the study of literature in the form of legal rules and theories of legal science and the Supreme Court Decision Number 460K/AG/2019. The results of the analysis of the judge's considerations in this decision concluded that first, based on the facts of the trial, Nadzir waqf was proven negligent or incompetent in the management of waqf, Second, that Judex facti had made a mistake in applying the law, so the judge granted the petition from the Plaintiff, namely canceling the Decision of the Religious High Court. Samarinda No. 36/Pdt.G/2018/PTA.Smd, and upheld the decision of the Tanah Grogot Religious Court Number 907/Pdt.G/2017/PA.Tgt.